Jivanmukti As Holiness In Hinduism - Conio, Caterina (Journal of Dharma, 1983)
Is there a definition or description of holiness which can embrace all of Hinduism regarding sanctity? Perhaps the most comprehensive description might be the following : The condition of holiness is the perfect transparency of the Supreme in a human being. The saint is one who is completely integrated in the Absolute and is aware of his oneness with God and creation; his behaviour will be, necessarily, the consequence of his realization.